'Defying Gravity': Prose Epic and Heroic Style in Lucrezia Marinella's 1602 Vita di Maria Vergine. (11th June 2021) - Brazeau, Bryan
Abstract: This article examines Lucrezia Marinella's literary-theoretical declaration at the beginning of the 1602 Vita di Maria Vergine by contextualizing her claims within contemporary debates on whether epic, particularly Christian epic, can be written in a style of high prose. It demonstrates that although Marinella seems to rely more heavily on Aristotle's Rhetoric, her choices in writing this epic in a high prose style were greatly influenced by the Poetics and contemporary discussions surrounding the text (along with a misunderstanding of the text itself). The essay also contains (as an appendix) the first English-language translation of Marinella's literary theoretical preface, 'To the Readers'.